Pemberdayaan Desa Binaan Berbasis Pengembangan Sentra Bawang Merah Unggul Ramah Lingkungan - Muhibuddin, Andi; Mahmud , Haris; Ilyas, M. Irham; Fada, Andi Tenri; Muhibuddin, Andi Firman (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2025)
This Empowerment Program for Assisted Villages aims to develop an environmentally friendly red onion production center. The environmentally friendly technologies used include the application of plant-based biopesticides, enhanced organic liquid fertilizers, and organic fungicides. The activities were carried out through several stages, namely: (1) program socialization, (2) training, (3) technology implementation, (4) mentoring and evaluation, and (5) program sustainability stages. The sustainability of this program involves providing in-kind assistance to farmer groups. Evaluation is carried out by administering pre-tests and post-tests to the targeted farmer groups. The program’s target farmer groups are the Anugerah farmer group (16.5 Ha) and the Passamuturukang farmer group (10.5 Ha).The results of this program implementation show that: (a) red onion productivity significantly; (b) the managerial ability of the farmer groups in managing red onion businesses increased; (c) the revenue of the farmer groups increased; (d) the knowledge of the farmer groups on seedling and red onion cultivation increased; and (e) the financial management understanding of the farmer groups increase. Based on these results, it can be concluded that this program successfully improved the farmers’ capacity and red onion production through the implementation of environmentally friendly technology.